2013
DOI: 10.1111/1462-2920.12323
|View full text |Cite
|
Sign up to set email alerts
|

HmsC, a periplasmic protein, controls biofilm formation via repression of HmsD, a diguanylate cyclase in Yersinia pestis

Abstract: Yersinia pestis, the cause of plague, forms a biofilm in the foregut of its flea vector to enhance transmission. Biofilm formation in Y. pestis is controlled by the intracellular levels of the second messenger molecule cyclic diguanylate (c-di-GMP). HmsT and Y3730, the two diguanylate cyclases (DGC) in Y. pestis, are responsible for the synthesis of c-di-GMP. Y3730, which we name here as HmsD, has little effect on in vitro biofilms, but has a major effect on biofilm formation in the flea. The mechanism by whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 40 publications
6
47
1
Order By: Relevance
“…We demonstrated that HmsC (a YfiR orthologue) inhibits HmsD (a YfiN orthologue)‐dependent c‐di‐GMP synthesis and biofilm formation in vitro (Figs and ). This independently confirms the recently published findings of Ren and colleagues (). However, we went one step further to demonstrate that HmsE (a YfiB orthologue) counteracts HmsC to promote the activity of the DGC HmsD.…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated that HmsC (a YfiR orthologue) inhibits HmsD (a YfiN orthologue)‐dependent c‐di‐GMP synthesis and biofilm formation in vitro (Figs and ). This independently confirms the recently published findings of Ren and colleagues (). However, we went one step further to demonstrate that HmsE (a YfiB orthologue) counteracts HmsC to promote the activity of the DGC HmsD.…”
Section: Discussionsupporting
confidence: 93%
“…yfiRNB are in a single operon in E. coli, and YfiR and YfiN have similar activities in E. coli as those in P. aeruginosa (51)(52)(53)59). Previous work has also shown that the YfiN homolog AwsR controls Pseudomonas fluorescens cellulose and biofilm formation (60), and in Yersinia pestis, the YfiN and YfiR homologs, HmsD and HmsC, respectively, contribute to biofilm formation and the blockage of blood intake in the rat flea Xenopsylla cheopis (61,62). The inhibition of YfiN by YfiR can be overcome in P. aeruginosa via overexpression of the outer membrane protein YfiB, which sequesters YfiR away from YfiN (53).…”
Section: Discussionmentioning
confidence: 99%
“…4A and B). In Y. pestis, biofilm formation was only modestly affected by deletion or overexpression of the YfiB homolog HmsE (61,62). In UPEC strain CFT073, yfiR deletion leads to an increase in cellulose and curli production along with attenuation of bladder and kidney titers in a murine urinary tract infection (UTI) model (52).…”
Section: Discussionmentioning
confidence: 99%
“…Major differences occur, however, in genes that control intracellular levels of cyclic-di-GMP, a bacterial signaling molecule that induces biofilm development (Hennge, 2009). Y. pseudotuberculosis encodes three GGDEF-domain diguanylate cyclases (DGC) that synthesize c-di-GMP and three EAL-domain phosphodiesterases (PDE) that degrade it (Bobrov et al, 2011; Ren et al, 2013; Sun et al, 2011). Notably, two of the three PDE genes ( rtn and y3389 , hereafter referred to as PDE2 and PDE3) are pseudogenes in Y. pestis; only hmsP (PDE1) is functional (Figure 1).…”
Section: Introductionmentioning
confidence: 99%